Determinants Of Factors Related To Inland Water Transport Safety Culture - PRIYONO, BROTO; WIJIANTO; PUSPITA SARI, YULIA; SUSANTO, NOVI TRI (Jurnal Penelitian Sekolah Tinggi Transportasi Darat, 2026)
Inland water transport safety is an important issue in the context of community mobility and goods transportation. However, inland water transport still faces various challenges in terms of safety. Data shows that accidents on inland water transport still occur frequently. Therefore, the development of a good safety culture among operators and users of inland water transport services is urgently needed. Safety culture is a concept that describes the attitudes, values, and behaviours of individuals and organisations in prioritising safety. Factors that can influence the safety culture of inland water transport crew members are knowledge culture and individual commitment. This study was conducted in Dramaga 16 Ilir, Palembang City, with a sample size of 100 inland water transport crew respondents. The results of the Structural Equation Model analysis concluded that individual knowledge does not significantly influence safety culture. Meanwhile, the factor of individual commitment has a positive and significant influence on the safety culture of inland water transport crews on the Musi River